Why individuals with trait anger and revenge motivation are more likely to engage in cyberbullying perpetration? The online disinhibition effect - Jin-liang Ding; Yan Lin; I-Hua Chen (Frontiers in Public Health)
BackgroundTrait anger has been identified as a significant risk factor in cyberbullying perpetration; however, the mechanisms underlying this relationship remain underexplored. This study aims to elucidate the connection between trait anger and cyberbullying perpetration among adolescents, with a focus on the mediating role of revenge motivation and the moderating effect of online disinhibition.MethodsA sample of 1,574 Chinese adolescents (46.1% female, mean age 16.89 years, SD = 0.34) participated in the study. Participants completed measures assessing trait anger, revenge motivation, online disinhibition, and cyberbullying perpetration.ResultsRevenge motivation partially mediated the association between trait anger and cyberbullying perpetration. Furthermore, the relationship between revenge motivation and cyberbullying perpetration, as well as the relationship between trait anger and cyberbullying perpetration, were moderated by online disinhibition, with a significant association observed only among adolescents exhibiting higher levels of toxic disinhibition.ConclusionThese findings extend the current understanding of cyberbullying perpetration among adolescents and offer valuable insights for intervention strategies targeting this antisocial online behavior.